Golgotha Cave stalagmite records 1 ka - Pauline C Treble; Andy Baker; Nerilie J Abram; John C Hellstrom; Jagoda Crawford; Michael K Gagan; Andrea Borsato; Alan D Griffiths; Petra Bajo; Monika Markowska; Stacey Priestley; Stuart I Hankin; et al. (PANGAEA, 2022)
Stalagmites GL-S1, GL-S2, GL-S3 and GL-S4 were collected under scientific license issued by Western Australia extquotesingles Department of Biodiversity, Conservation and Attractions from Golgotha Cave (34.1°S, 115.1°E) in southwest Western Australia, with collection dates of 2005, 2005, 2008 and 2012, respectively. Cave location is rounded to nearest tenth of a degree as exact locations not disclosed for cave conservation purposes. Speleothems were collected for paleoclimate and paleohydrology studies. Golgotha Cave is located in Eucalyptus forest with dense understorey in the Leeuwin-Naturaliste National Park. The hostrock is Quaternary aeolinite and the soil thickness is variable with measurements ranging from 0.3-3 m deep. The cave entrance is 70 m above sea level. Stalagmites GL-S1 and GL-S4 are located approximately 60 m from the entrance where the limestone thickness overhead is 30 m while GL-S2 and GL-S3 are located approximately 90 m from the entrance where the limestone thickness overhead is 40 m. Mean annual site temperature is 15.6 ±0.5°C and mean annual rainfall is 1101±157 mm (1911-2018 period; Australian Bureau of Meteorology AWRA-L dataset http://www.bom.gov.au/water/landscape. Inside the cave, temperature ranges from 14.5-14.8°C, windspeed is low (≤0.03 m s-1) and relative humidity ranges from 98-100% (Treble et al 2019). Each speleothem was sectioned along the growth axis and milled using a Taig micromill to produce homogenised powders representing increments of 0.1 to 0.2 mm, depending on the speleothem growth rate. Powders were weighed to 180–220 μg and analysed for O and C isotopic values (δ18O and δ13C) using a Finnigan MAT-251 isotope ratio mass spectrometer coupled to a Kiel I carbonate device, or a Thermo MAT-253 isotope ratio mass spectrometer coupled to a Kiel IV carbonate device (using 110–130 μg samples), at the Research School of Earth Sciences, ANU. Analyses were calibrated using NBS-19 standard (δ18Ov-PDB = -2.20 extperthousand and δ13Cv-PDB = 1.95 extperthousand). A further linear correction for δ18O measurements was carried out using the NBS-18 standard (δ18Ov-PDB = -23.0 extperthousand). The original delta values for NBS-19 and NBS-18 are used to maintain consistency of results through time in the RSES Stable Isotope Facility. Analytical precision for the analyses reported here (NBS-19) are ±0.04 extperthousand for δ18O and ±0.02 extperthousand for δ13C (N=236) for the MAT-251; and ±0.05 extperthousand for δ18O and ±0.01 extperthousand (N=27) for the MAT-253 instrument (±1σ standard deviation). Speleothem chronologies were determined by combining information from the date of collection, bomb pulse chronology, laminae counting of annual Sr concentration and U-series disequilibrium (see Supplementary Table 8 in Treble et al., 2022). For GL-S1, the age-depth model for 17th percentile was used in Treble et al., (2022) and the 50th percentile used for other stalagmites.